Protective Mechanism of Rosa roxburghii Tratt Fermentation Broth against Ultraviolet-A-Induced Photoaging of Human Embryonic Skin Fibroblasts - Minglu Yuan; Hao Fu; Qiuting Mo; Shiwei Wang; Changtao Wang; Dongdong Wang; Jiachan Zhang; Meng Li (MDPI AG, 2024)
This study takes the fruit of Rosa roxburghii Tratt (RRT) as a fermentation substrate and carries out a quantitative visual analysis of the domestic and foreign literature on screenings of five different lactic acid bacteria to obtain a fermentation broth. Systemic anti-photoaging effects are analyzed at the biochemical, cellular, and molecular biological levels. DPPH and ABTS free radical scavenging activities are used to verify the antioxidant capacity of the RRT fruit fermentation broth in vitro. Human embryonic skin fibroblasts (HESs) are used to establish a UVA damage model, and the antioxidant capacity of the RRT fruit fermentation broth is verified in terms of intracellular reactive oxygen species (ROS) and antioxidant enzyme activity. RT-qPCR and ELISA are used to detect the expression of TGF-β/Smad, MMPs, and the MAPK/AP-1 and Nrf2/Keap-1 signaling pathways in order to explore the anti-oxidation and anti-photoaging effects of the RRT fruit fermentation broth by regulating different signaling pathways. The results show that an RRT fruit fermentation broth can effectively protect cells from oxidative stress caused by UVA and has significant anti-photoaging effects, with the co-cultured Lactobacillus Yogurt Starter LYS-20297 having the highest overall effect.